Implicit argumentation as a patemization strategy - Welton Pereira e Silva; Lúcia Helena Martins Gouvêa (Gragoatá, 2020)
This paper aims to demonstrate how, through implicit meanings, the arguing subject can lead the interpreting subject to experience certain emotions. For this, we analyze a journalistic chronicle written by Luiz Garcia in light of the theoretical and methodological postulates of the Semiolinguistic Theory of Discourse, proposed by Patrick Charaudeau, as well as of Ducrot and Anscombre's Theory of Argumentation in Language. We realized that various presupposed and implicit contents, that is, implicit meanings, presented by the enunciator subject of the chronicle, are capable of producing certain pathemic effects on the interpreting subject, depending on their values and beliefs. In the textual argumentative project, the patemization contributes to the capture of the reader, possibly leading him to accept the thesis defended by the enunciator.